First results from the JWST early release science program Q3D: the warm ionized gas outflow in z ∼ 1.6 quasar XID 2028 and its impact on the Host Galaxy - Veilleux, Sylvain; Liu, Weizhe; Vayner, Andrey; Wylezalek, Dominika; Rupke, David S. N.; Zakamska, Nadia L.; Ishikawa, Yuzo; Bertemes, Caroline; Barrera-Ballesteros, Jorge K.; Chen, Hsiao-Wen; Diachenko, Nadiia; Goulding, Andy D.; et al. (The astrophysical journal, 2023)
Quasar feedback may regulate the growth of supermassive black holes, quench coeval star formation, and impact galaxy morphology and the circumgalactic medium. However, direct evidence for quasar feedback in action at the epoch of peak black hole accretion at z ≈ 2 remains elusive. A good case in point is the z = 1.6 quasar WISEA J100211.29+013706.7 (XID 2028), where past analyses of the same ground-based data have come to different conclusions. Here, we revisit this object with the integral-field unit of the Near Infrared Spectrograph on board the JWST as part of Early Release Science program Q3D. The excellent angular resolution and sensitivity of the JWST data reveal new morphological and kinematic substructures in the outflowing gas plume. An analysis of the emission-line ratios indicates that photoionization by the central quasar dominates the ionization state of the gas with no obvious sign for a major contribution from hot young stars anywhere in the host galaxy. The rest-frame near-UV emission aligned along the wide-angle cone of outflowing gas is interpreted as a scattering cone. The outflow has cleared a channel in the dusty host galaxy, through which some of the quasar ionizing radiation is able to escape and heat the surrounding interstellar and circumgalactic media. Although the warm ionized outflow is not powerful enough to impact the host galaxy via mechanical feedback, radiative feedback by the active galactic nucleus, aided by the outflow, may help to explain the unusually small molecular gas mass fraction in the galaxy host.
Online veröffentlicht: 2 August 2023
Gesehen am 11.10.2023